2015
DOI: 10.1016/j.apjtm.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low intensity pulsed ultrasound on expression of TIMP-2 in serum and expression of mmp-13 in articular cartilage of rabbits with knee osteoarthritis

Abstract: The inner patellar ligament defect method is a mature method to establish the rabbit OA model, with high success rate. The expression of serum TIMP-2 in the OA model group is significantly decreased. LIPUS can up-regulate TIMP-2 and down-regulate MMP-13.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 14 publications
3
17
0
Order By: Relevance
“…The results showed that the expression of caspase-3 was inhibited in chondrocytes cocultured with ADSCs group and TGF- β 1-containing culture medium group (Figures 8(a), 8(b), and 8(c)). Some studies have indicated that some matrix metalloproteinase (MMP) such as MMP3 and MMP13 can damage the chondrocytes [15, 16]. Our results showed that ADSCs reduced the destruction of matrix metalloproteinase in chondrocytes.…”
Section: Resultssupporting
confidence: 55%
“…The results showed that the expression of caspase-3 was inhibited in chondrocytes cocultured with ADSCs group and TGF- β 1-containing culture medium group (Figures 8(a), 8(b), and 8(c)). Some studies have indicated that some matrix metalloproteinase (MMP) such as MMP3 and MMP13 can damage the chondrocytes [15, 16]. Our results showed that ADSCs reduced the destruction of matrix metalloproteinase in chondrocytes.…”
Section: Resultssupporting
confidence: 55%
“…Two studies showed no significant improvements in cartilage volume/thickness [18,35], but one of these further demonstrated significant improvement in pain and function after LIPUS treatment [18]. One study showed a significant increase in tissue inhibitor of metalloproteinase (TIMP) expression in LIPUS‐treated groups [30]. One study demonstrated a significant increase in CPII and a nonsignificant decrease in CTX‐II [7].…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies evaluated the effect of LIPUS on expression of MMP-13, a protein involved in cartilage degradation that is overexpressed in osteoarthritis [16,[22][23][24]26,28,30,31]. These were all randomized controlled trials involving animal models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jing-Bo Ji et al [17] confirmed that the expression of serum TIMP-2 is significantly decreased in an animal model of OA. Fang-Jie Zhang et al [18] carried out an in vitro experimental study using tissue samples from 16 Chinese patients with knee OA and identified mRNA expression of TIMP-1 and TIMP-2 significantly increased cytotoxicity or apoptosis of chondrocytes.…”
Section: Introductionmentioning
confidence: 99%